Meningkatkan Hasil Belajar Pendidikan Agama Katolik Dan Budi Pekerti Model Problem Based Learning (PBL) Berbantuan Case Study Materi Kesetaraan Laki-Laki Dan Perempuan Kelas X Sma Santa Maria 1 Cirebon - Kristofarus Dion Angga Permana; Sukestiyarno Sukestiyarno; Murlani Murlani (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aimed to improve the student’s outcames of the X-2 grade F phase SMA Santa Maria 1 Cirebon year of 2024/2025 in Catholic religious and morals subjects by implementating Problem Based Learning (PBL) model assisted by case study. This research is a classroom action research that included in two cycle with 2 confluence every cycle. Each cycle consist of planning, acting, observing, and reflecting. The first and second cycle discussed the subject of gander equality. The subject of this research is student of X-2 grade F phase SMA Santa Maria 1 Cirebon year of 2024/2025 which consist of 28 students. The main technique in data collecting used test, and observation, meanwhile the proponent technique used interview and documentation. The result of this research showed that the implementation of Problem Based Learning model assisted by case study can improve learning outcomes student of X-2 grade F phase in Catholic religious and morals subjects start from cycle I and cycle II is 77 in cycle I stage increase to be 83 in cycle II. The conclution of this research is the implementation of Problem Based Learning (PBL) model assisted by case study can improve learning outcomes student of X 2 grade F phase SMA Santa Maria 1 Cirebon year of 2024/2025.